(untitled) (Revista de Ciências Agroveterinárias, 2017)
use of soluble phosphates and rock phosphates is a normal practice in Eucalyptus fertilization. As the phosphorus fertilizer is located near the plant, phosphorus (P) may interfere with the growth and morphology of the root system. The objective of this work was to evaluate the growth and morphological characteristics of root system of Eucalyptus dunnii using soluble and rock phosphate. Samples were collected in 2013 from an experiment established in 2010 in the city of Otacílio Costa, SC. Samples were collected from four treatments: 1) control without P; 2) fertilization with 60 kg ha-1 of P2O5 in the form of phosphate rock; 3) 75 kg ha-1 of P2O5 in the form of triple superphosphate and; 4) 60 kg ha-1 rock phosphate P2O5 plus 75 kg ha-1 P2O5 soluble phosphate (these doses being chosen because it represents the usual practice in the reforestation of the region). The collection of roots occurred 28 months after planting of the seedlings and application of treatment with a 40 mm in diameter and 100 mm high probe. The soil and root samples were collected at three distances from the shaft (10, 60 and 120 cm) and two layers (0-10 and 10-20 cm). The roots were separated in two diameter classes: 0 to 2 mm and 2 to 5 mm. Dry matter of roots were characterized, root radius, length, volume and root area. Rock phosphate did not stimulate root growth and the soluble phosphate was the source that improved growth and development of fine roots in Eucalyptus dunnii, with the highest concentration of these roots being located near the shaft and in the most superficial layer of soil.